Caribbean Report 15-01-1993 - Jarvis, Mike (anchor); Adams, David (correspondent); Blanchard, Ernest J. (interviewee); Burns, Larry (interviewee); Fenton, John (correspondent); Durance, Roland (interviewee); Khan, Bobby (interviewee) (The British Broadcasting Corporation, 1993)
The US coastguard launches operation “Able Manner.” This is a major operation to intercept Haitian refugees (aka Haitian boat people) seeking asylum in the US, as a precautionary measure to save their lives. The reaction to this move is mixed. Anchor Mike Jarvis interviews professor Larry Burns on this issue and gives his views on President Clinton’s policy as a public relations disaster. In an interview, correspondent David, Adams gets the views of Ernest J. Blanchard - Captain, US Coast Guard on the US Coast Guard’s approach to operation Able Manner in dealing with the refugees. The Barbados manufacturing industry welcomed the repeal of some of the taxes waived, but wants the government to do more for them in order to stimulate the industry - Mike Jarvis reports. The Trinidad golfer Stephen Aimes is off to a good start on the European competition circuit in Madeira Island’s - Golf Open in the PGA. He was the first Caribbean player to take part in the PGA European tour, having gained the respect of the pros at the event with a share of 6th place along with 5 other players amidst the challenging strong winds on the golf course.
Headlines (00:00-00:30) )
1. The US coastguard launches operation “Able Manner.” This is a major operation to intercept Haitian refugees (aka Haitian boat people) seeking asylum in the US, as a precautionary measure to save their lives. The reaction to this move is mixed. Anchor Mike Jarvis interviews professor Larry Burns on this issue and gives his views on President Clinton’s policy as a public relations disaster. In an interview, correspondent David, Adams gets the views of Ernest J. Blanchard - Captain, US Coast Guard on the US Coast Guard’s approach to operation Able Manner in dealing with the refugees (00:31 -10:51).
2. The Barbados manufacturing industry welcomed the repeal of some of the taxes waived, but wants the government to do more for them in order to stimulate the industry - Mike Jarvis reports (10:52–12:59).
3. The Trinidad golfer Stephen Aimes is off to a good start on the European competition circuit in Madeira Island’s - Golf Open in the PGA. He was the first Caribbean player to take part in the PGA European tour, having gained the respect of the pros at the event with a share of 6th place along with 5 other players amidst the challenging strong winds on the golf course (01:00-14: 54).
Keywords: Haiti—Foreign Relations—United States.; Haitian—Refugees—United States.; United States--Emigration and immigration.; Barbados--Commerce.; Barbados Manufacturing Association.; Barbados--social conditions.; Barbados--economic conditions.; Trinidad and Tobago—Golf.; Aimes, Stephen.